Elimination of Viroids from Tobacco Pollen Involves a Decrease in Propagation Rate and an Increase of the Degradation Processes - Matoušek, Jaroslav; Steinbachová, Lenka; Drábková, Lenka Záveská; Kocábek, Tomáš; Potěšil, David; Mishra, Ajay Kumar; Honys, David; Steger, Gerhard (International journal of molecular sciences, 2020)
Some viroids-single-stranded, non-coding, circular RNA parasites of plants-are not transmissible through pollen to seeds and to next generation. We analyzed the cause for the elimination of apple fruit crinkle viroid (AFCVd) and citrus bark cracking viroid (CBCVd) from male gametophyte cells of Nicotiana tabacum by RNA deep sequencing and molecular methods using infected and transformed tobacco pollen tissues at different developmental stages. AFCVd was not transferable from pollen to seeds in reciprocal pollinations, due to a complete viroid eradication during the last steps of pollen development and fertilization. In pollen, the viroid replication pathway proceeds with detectable replication intermediates, but is dramatically depressed in comparison to leaves. Specific and unspecific viroid degradation with some preference for (-) chains occurred in pollen, as detected by analysis of viroid-derived small RNAs, by quantification of viroid levels and by detection of viroid degradation products forming "comets" on Northern blots. The decrease of viroid levels during pollen development correlated with mRNA accumulation of several RNA-degrading factors, such as AGO5 nuclease, DICER-like and TUDOR S-like nuclease. In addition, the functional status of pollen, as a tissue with high ribosome content, could play a role during suppression of AFCVd replication involving transcription factors IIIA and ribosomal protein L5.
Keywords: nemoci rostlin; Phenotype; virová nálož; RNA, Viral; Nicotiana; replikace viru; viroidy; Nucleic Acid Conformation; konformace nukleové kyseliny; RNA virová; Viral Load; Pollen; Plant Diseases; pyl; Viroids; interakce hostitele a patogenu; fenotyp; Host-Pathogen Interactions; Virus Replication; tabák